STUDI KASUS PENILAIAN HOTEL DI BALI - I Wayan Priyana Agus Sudharma (Yayasan Nusantara Hasana Berdikari, 2023)
The recovery of the Bali tourism sector has had a positive impact on the economy and investment climate. Post-pandemic, there has been an increase in credit growth in the Province of Bali as a result of an increase in working capital credit and consumption credit, and investment credit. Valuation of collateral properties assists banks in determining the market value of property used as collateral for debt. This value is used as a reference in determining the amount of loan that can be given and the appropriate level of security. The object of the case study is a hotel with an appraisal using the income approach, the discounted cash flow (DCF) method, resulting in a property value of IDR 56,500,000,000.00